Political Background, Transparansi Kebijakan Publik, Pengetahuan Dewan Tentang Anggaran dan Peran DPRD Dalam Pengawasan Keuangan Daerah - Made, Asri Millifanny Aryastuti; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi, 2024)
The purpose of this study was to analyze the influence of Political Background, Transparency of Public Policy and Knowledge of the Council on Budgets on the Role of DPRD in Regional Financial Supervision (APBD) of Badung Regency and Klungkung Regency. The population in this study were 70 people. The sampling method used in this study is a non-probability sampling method with a saturated sampling technique with multiple regression analysis techniques. The results showed that political background, transparency of public policies and knowledge of DPRD members had a positive effect on the role of DPRD in regional financial supervision and had a positive effect on DPRD's role in regional financial supervision. Referring to the research findings, DPRD members should always maintain the political background, increase public policy transparency and increase knowledge about the budget. Keywords: Political Background; Public Policy Transparency; Board Knowledge; Regional Financial Supervision